2021
DOI: 10.22401/anjs.24.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Effecient Photo-Stabilizers: By Using Medications As Ligands Connected to Oragontin(IV) Complexes

Abstract: Organotin materials have several applications in industry and medicine since it uses to prepare medications. Moreover, it is used as photo-stabilizers for different plastic polymers such as polyvinyl chloride, polystyrene, and polyvinyl alcohol. Herein, it is going to focus on one application which is utilizing organotin complexes as photo-stabilizers of polyvinyl chloride. Since organotin(IV) can easily obtained by oxidizing organotin(II) that is more stable. Organotin(IV) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recently, researchers used either medicine or pharmaceutical intermediates as raw materials to prepare Organotin. Yousif et al [ 24 ] reported the synthesis of efficient photo‐stabilizers by using medications as ligands that were connected to organotin (IV) complexes. Bufaroosha et al [ 25 ] synthesized four organotin (IV) complexes from the reaction of the tin (IV) chloride salts and telmisartan.…”
Section: Common Thermal Stabilizersmentioning
confidence: 99%
“…Recently, researchers used either medicine or pharmaceutical intermediates as raw materials to prepare Organotin. Yousif et al [ 24 ] reported the synthesis of efficient photo‐stabilizers by using medications as ligands that were connected to organotin (IV) complexes. Bufaroosha et al [ 25 ] synthesized four organotin (IV) complexes from the reaction of the tin (IV) chloride salts and telmisartan.…”
Section: Common Thermal Stabilizersmentioning
confidence: 99%